Milne Fiord CTD (Conductivity, Temperature, Depth) profiles, 2008-2019 ... - Mueller, Derek; Antropova, Yulia; Bonneau, Jérémie; Brenner, Sam; Copland, Luke; Crocker, Greg; De Jong, Tyler; Forrest, Alexander; Friedrichs, Drew; Garbo, Adam; Graves, Kelly; Hamilton, Andrew; et al. (Canadian Cryospheric Information Network, 2021)
Conductivity, Temperature, Depth (CTD) profiles taken in Milne Fiord. Profiles were taken either in the spring (April to May) or the summer (June to August) timeframe. In the spring, typically the water column was accessed through a hole in the ice. In the summer, it is sometimes possible to find pre-existing holes. ... : CTD profiles were conducted to examine the oceanography of Milne Fiord from the glacier grounding line to the open ocean. These casts can be used to determine the depth of the epishelf lake (see data from Warwick Vincent as well), but they were also collected to examine variability along and across the fiord, to infer the position and height of topographic sills, to look for deep water renewal events and to examine the amount of melt water from the glacier, ice shelf or watershed. ...